The effect of glia-glia interactions on oligodendrocyte precursor cell biology during development and in demyelinating diseases - Clemente, Diego; Ortega, María Cristina; Melero-Jerez, Carolina; De Castro, Fernando (Frontiers in Cellular Neuroscience, 2013)
Oligodendrocyte precursor cells (OPCs) originate in specific areas of the developing central nervous system (CNS). Once generated, they migrate towards their destinations where they differentiate into mature oligodendrocytes. In the adult, 5-8% of all cells in the CNS are OPCs, cells that retain the capacity to proliferate, migrate and differentiate into oligodendrocytes. Indeed, these endogenous OPCs react to damage in demyelinating diseases, like multiple sclerosis (MS), representing a key element in spontaneous remyelination. In the present work, we review the specific interactions between OPCs and other glial cells (astrocytes, microglia) during CNS development and in the pathological scenario of MS. We focus on: i) the role of astrocytes in maintaining the homeostasis and spatial distribution of different secreted cues that determine OPC proliferation, migration and differentiation during CNS development; ii) the role of microglia and astrocytes in the redistribution of iron, which is crucial for myelin synthesis during CNS development and for myelin repair in MS; iii) how microglia secrete different molecules, e.g. growth factors, that favor the recruitment of OPCs in acute phases of MS lesions; and iv) how astrocytes modify the extracellular matrix in MS lesions, affecting the ability of OPCs to attempt spontaneous remyelination. Together, these issues demonstrate how both astroglia and microglia influence OPCs in physiological and pathological situations, reinforcing the concept that both development and neural repair are complex and global phenomena. Understanding the molecular and cellular mechanisms that control OPC survival, proliferation, migration and differentiation during development, as well as in the mature CNS, may open new opportunities in the search for reparative therapies in demyelinating diseases like MS.